Assessment of the Effect of Temperature and Annealing Time on Homogenization of AlCu4MgMn Alloys - Weiss, V. (Металлофизика и новейшие технологии, 2013)
Homogenization is defined as a method of heat treatment, which consists of holding time at high temperature near the liquidus (approx. 0.7 to 0.8 of the melting temperature) to eliminate chemical inhomogeneity diffusion processes. Cause of segregation is selective crystal solidification in the gradual change in composition of the solid phase. Melt began to appear after certain hypothermia during cooling, and the growth of germs in accordance with the general laws of crystallization. Each rigid layer has a different chemical composition. The first part of the solid phase ingredient is characterized with low concentration of the element, the last one, on the contrary, is characterized with very high concentration. Susceptibility to crystal alloy segregation is greater, when the temperature interval solidification of alloys and the horizontal distance between the liquidus and solidus lines are larger. Crystal segregation will also increase with increasing content of alloying elements, which occurs in these experimental alloys as containing 6—9% alloying elements. Crystal segregation can be removed by diffusion, for which it is necessary to create conditions by homogenization annealing.